Evaluation of Antioxidant and Cytotoxicity Activities of Mimosa pudica Linn. Leaf Extract Combined with Silver Nanoparticles (AgNPs) Against Human Colorectal Cancer HCT116 Cell - Rahmad Fajral Ilhami; Dian Pertiwi; Dessy Arisanty; Yanti Rahayu (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Colorectal cancer is one of the leading causes of cancer-related morbidity and mortality worldwide, with oxidative stress playing a pivotal role in colorectal carcinogenesis. The limitations of conventional therapies, including systemic toxicity and drug resistance, have driven the exploration of alternative therapeutic agents derived from natural products. Mimosa pudica Linn. leaves are known to contain bioactive compounds with antioxidant and anticancer properties; however, their clinical application is limited by poor biopharmaceutical characteristics. The combination of Mimosa pudica leaf extract with silver nanoparticles (AgNPs) is expected to enhance its biological efficacy through nanotechnology-based drug delivery systems. This study was conducted as an in vitro experimental investigation. Mimosa pudica Linn. leaf extract was prepared using an extraction method and subsequently combined with silver nanoparticles. Antioxidant activity was evaluated using the DPPH assay, with ascorbic acid serving as a positive control. Cytotoxic activity against the human colorectal cancer cell line HCT116 was assessed using the MTT assay to determine cell viability and IC50 values. Statistical analyses were performed to evaluate differences among treatment groups. The results demonstrated that Mimosa pudica Linn. leaf extract exhibited significant antioxidant activity, although it was lower than that of ascorbic acid. In cytotoxicity assays, the leaf extract reduced HCT116 cell viability in a dose-dependent manner. Notably, the combination of Mimosa pudica leaf extract with silver nanoparticles produced a more pronounced cytotoxic effect compared to the extract alone, as indicated by a greater reduction in cell viability and lower IC50 values. In conclusion, Mimosa pudica Linn. leaf extract possesses antioxidant and cytotoxic activities against HCT116 colorectal cancer cells. Its combination with silver nanoparticles enhances cytotoxic potency, highlighting its potential as a nanomedicine-based anticancer candidate for colorectal cancer therapy.